2005
DOI: 10.1111/j.1443-9573.2005.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer: Worldwide burden and prevention opportunities

Abstract: Gastric cancer is a major worldwide problem in developing and developed countries. It contributes substantially to the economic medical resource burden and population mortality in many countries. The absolute numbers of new cases of death are expected to increase significantly over the next decades because of the enlarging and aging of the world population. The putative factors are better understood today, and control of these factors, together with screening can help prevent this cancer from becoming an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…GC is a major contributor to the global cancer burden with about 50% of GC cases and deaths occur in China. 26,27 Recently, accumulating studies showed that non-coding RNAs including lncRNAs and miRNAs could function as potential tumor markers or therapeutic targets in GC. 28,29 LncRNA XIST has been reported to be an oncogenic factor in GC.…”
Section: Discussionmentioning
confidence: 99%
“…GC is a major contributor to the global cancer burden with about 50% of GC cases and deaths occur in China. 26,27 Recently, accumulating studies showed that non-coding RNAs including lncRNAs and miRNAs could function as potential tumor markers or therapeutic targets in GC. 28,29 LncRNA XIST has been reported to be an oncogenic factor in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is one of the most important problems and the second leading cause of cancer-related death in industrialized and developing countries. 1 Incidence and mortality of gastric cancer in some countries such as Japan, China, Korea, South Africa, northern France and Iran are higher than those of other regions of the world. 2 Gastric cancer is a deceptive disease and frequently asymptomatic and diagnosed at late stages of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer continues to be a major health problem worldwide , , and current systemic therapies for gastric cancer are often limited by their short-term efficacy due to the side effects , . There are growing interests in the treatment of cancers by using naturally occurring compounds with chemopreventive and chemotherapeutic properties .…”
Section: Introductionmentioning
confidence: 99%